2016
DOI: 10.1002/ajpa.23033
|View full text |Cite
|
Sign up to set email alerts
|

Oral microbiome diversity among Cheyenne and Arapaho individuals from Oklahoma

Abstract: The C&A and NNI participants from Oklahoma have notable differences in their microbiome diversity, with a wider range of variation observed among the C&A individuals, including a higher frequency of bacteria implicated in systemic disorders. Overall, this study highlights the importance of engagement with indigenous communities, and the need for an improved understanding of human microbiome diversity among underrepresented groups and those individuals living outside of metropolitan areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…However, our fundamental understanding of contemporary microbiome alterations requires recognition of the current ascertainment bias; the majority of microbiome studies examine populations of European descent, who live industrialized lifestyles (Lewis et al, ; Warinner & Lewis, ). The little existing research on different ethnic populations has shown that there are taxonomic, compositional, and functional differences in the microbiomes of different human populations (Anwesh et al, ; Martínez et al, ; Ozga et al, ; Rampelli et al, ; Yatsunenko et al, ; Zhang et al, ). Therefore, it cannot be assumed that the same instigator will equally impact different microbiomes; dysbiosis may take different forms, provoking various disease responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, our fundamental understanding of contemporary microbiome alterations requires recognition of the current ascertainment bias; the majority of microbiome studies examine populations of European descent, who live industrialized lifestyles (Lewis et al, ; Warinner & Lewis, ). The little existing research on different ethnic populations has shown that there are taxonomic, compositional, and functional differences in the microbiomes of different human populations (Anwesh et al, ; Martínez et al, ; Ozga et al, ; Rampelli et al, ; Yatsunenko et al, ; Zhang et al, ). Therefore, it cannot be assumed that the same instigator will equally impact different microbiomes; dysbiosis may take different forms, provoking various disease responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, African populations were characterized by a less diverse saliva microbiome than rural individuals from Alaska or urban individuals from Germany 35 , thus opposite to the trends observed for the gut microbiome. Similarly, the saliva microbiome of Native Americans in Oklahoma had lower diversity than the microbiome of neighbouring more urbanized individuals of European descent 36 . Finally, Clemente et al 3 found no difference between the saliva microbiome of the isolated Yanomami population from Venezuela and individuals from the US (despite differences in their gut microbiome diversity), suggesting no effect of lifestyle.…”
mentioning
confidence: 99%
“…mutans GTs between two different populations separated by geography and ethnicity but with similar SES. However, a very recent paper compared the oral microbiome diversity among Cheyenne and Arapaho individuals in Oklahoma (Ozga, Sankaranarayanan, Tito, et al, ). While there was not an emphasis on S .…”
Section: Discussionmentioning
confidence: 99%